Efficient Incremental Data Modeling in Apache Iceberg-Based Analytical Pipelines: Partitioning and Snapshot Optimization Strategies (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2026)
Lakehouse relies on Apache Iceberg to efficiently handle big data analytics in a reliable and scala-able way. But inefficient incremental modeling has the capacity of decreasing the speed of queries and hiking the cost of storage in the long run. This paper gives a quantitative assessment of the partitioning and snapshot retention and compaction policies in terms of Monte Carlo simulations. Findings indicate that scans shrink percentage was increased day to day using partitioning (0.61 to 0.82) and reaction savings were decreased (18.4 seconds to 13.4 seconds). Snapshot expiration policies decreased metadata to data ratio (0.18 to 0.07) and reduced the overall query response (19.3 seconds to 15.8 seconds). Threshold based and daily compaction ensured that average file sizes were above 240 MB and overall efficiency score increased by 0.032 as compared to 0.051. Connected optimization minimized the overall latency by 34 per cent and storage fragmentation by 41 per cent. The results offer viable suggestions in the development of robust and viable Iceberg analytical pipelines.
Keywords: Apache Iceberg; Incremental Data Modeling; Lakehouse Architecture; Partition Evolution; Metadata Optimization